The earth giant - Burgess, Melvin (New York : Andersen Press Limited, 1995)
When Peter and his sister discover a giant extraterrestrial hidden beneath the earth, they become friends and conspirators despite the tremendous risks involved.
Keywords: Extraterrestrial beings -- Fiction; Brothers and sisters -- Fiction; Science fiction